2022
DOI: 10.3390/microorganisms10050961
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton Surveys in the Arctic Fram Strait Demonstrate the Tiny Eukaryotic Alga Micromonas and Other Picoprasinophytes Contribute to Deep Sea Export

Abstract: Critical questions exist regarding the abundance and, especially, the export of picophytoplankton (≤2 µm diameter) in the Arctic. These organisms can dominate chlorophyll concentrations in Arctic regions, which are subject to rapid change. The picoeukaryotic prasinophyte Micromonas grows in polar environments and appears to constitute a large, but variable, proportion of the phytoplankton in these waters. Here, we analyze 81 samples from the upper 100 m of the water column from the Fram Strait collected over m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 62 publications
3
13
1
Order By: Relevance
“…This suggestion is supported by the lack of a relationship between available food and chlorophyll a (add details of correlation (or lack thereof) here). This disparity is also potentially attributable to the high abundances of picoplankton (≤2 µm cell diameter) that have been reported to occur in the Fram Strait, in particular the Micromonas genus of prasinophytes (Bachy et al, 2022), that were not enumerated in our study.…”
Section: Ingestionmentioning
confidence: 71%
“…This suggestion is supported by the lack of a relationship between available food and chlorophyll a (add details of correlation (or lack thereof) here). This disparity is also potentially attributable to the high abundances of picoplankton (≤2 µm cell diameter) that have been reported to occur in the Fram Strait, in particular the Micromonas genus of prasinophytes (Bachy et al, 2022), that were not enumerated in our study.…”
Section: Ingestionmentioning
confidence: 71%
“…Though our dataset is limited, it suggests that Micromonas could become increasingly important in coastal regions as tidewater submarine discharge and its associated nutrient delivery to surface water declines in the future. However, though smaller phytoplankton species, like Micromonas , have not traditionally been considered major players in carbon export from the surface ocean, new evidence shows this could change when Micromonas makes up the majority of the phytoplankton community (Bachy et al 2022). Data from Fram Strait reveals Micromonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…Even though it appears to be growing well at 6 °C [ 91 ] and has shown a high adaptation potential to warming [ 92 ], its population may crash rapidly if temperatures exceed this upper limit. Studies have shown the importance of this genus to overwintering standing stocks and deep-sea export [ 93 , 94 , 95 ], indicating consequences for the ecosystem if temperatures rise to 9 °C.…”
Section: Discussionmentioning
confidence: 99%